المرأة بالمغرب الأوسط بين التأتير و التأثر خلال القرنين(6-9 هـ/12-15 م) - صالحي, وداد (Universty of Eloued جامعة الشهيد حمة لخضرالوادي, 2021)
خلاصة: تبحث الدراسة إلى أي مدى تشارك المرأة في البناء و تصنيع النهضة الثقافية لدول المغرب العربي ، وكيف كان لها تأثير على تلك الأحداث التي مرت بالمنطقة من خلال ، تتأثر ، مثل أي شخص آخر ، بآخر التطورات من حولها. تهدف الدراسة إلى تسليط الضوء على جانب مهم من تاريخ المرأة و التأثير المتبادل مع الحضارة الخفية للشرق الأوسط ، جنبًا إلى جنب مع نظرة متعمقة على الجانب الاجتماعي للمرأة في الشرق الأوسط ، لأن هذا الموضوع بجانبيه (نساء) و (المغرب الأوسط) مهم جدا في مصطلحات التاريخ الاجتماعي لفهم التحولات الثقافية للمجتمعات في ذلك المنطقة ، ولمعرفة المزيد عن التأثير المتبادل بين المرأة والدين والعرف داخل المجتمع المغاربي. من هذه النقطة نريد أن نجيب على مشكلة الدراسة التي هي ما يلي: إلى أي مدى تأثرت المرأة وتأثرت بها في منطقة المغرب الأوسط خلال القرنين (6-9 هـ / 12-15 م). Abstract: The study examines to what extent woman participates in building and manufacturing the cultural renaissance of the Countries of the Middle Maghreb, and how she has had an influence on those events that the region has passed through, influenced, as anyone else, by the latest developments around her. The study aims to highlight an important aspect of woman's history and mutual influence with the hidden civilization of the Middle East, along with an in-depth sight on the social aspect of women in the Middle East, because this topic with its two sides (women) and (Middle Morocco) is very important in terms of social history to understand the cultural turns of the societies of that region, and to learn more about the mutual influence between women, religion and custom within The Maghreb society. From this point, we want to answer the problem of the study which is as follows: to what extent woman has influenced and has been influenced by in the Middle Maghreb during the two centuries (6-9 Ah / 12-15 AD).
أطروحة دكتوراه تخصص تاريخ المغرب الوسيط والحديث في العلوم الإجتماعية و الإنسانية
Keywords: المرأة بيف الكساطة كاالستشارة/دور المرأة الفكري والعممي وتأثيرىا عمى مجتمع المغرب األوسط/أثر المرأة عمى مجتمع المغرب الوسط ومظاهره; Women between mediation as counseling / the intellectual and scientific role of women and their impact on the central Maghreb society / the impact of women on the central Maghreb society and its manifestations